Improving Health through Education about Clean and Healthy Living Behavior (CHLB) in The Household - Yulis, Rahma; Wahyuni, Andi; Syam, Ilham; M, Renaldi; Njortetma, Alfredo A (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2024)
Perilaku Hidup Bersih dan Sehat (PHBS) or Clean and Healthy Living Behavior (CHLB) is a special program from the Indonesian government. Clean and Healthy Living Behavior must be implemented in all places: in households, educational institutions, workplaces, public places and health service facilities. The aim of this activity is to improve public health through providing education in households. Implementation of this activity consists of four stages: determining the location and time of the activity, preparing material, implementing the activity, and preparation of the activity report. The first stage begins with coordinating the community service team with cadres and village officials. The second stage is the preparation of educational material including: understanding, objectives, benefits, and ten indicators of household CHLB. The third stage provides education using the lecture method on